Financial shocks and inflation dynamics - Angela Abbate; Sandra Eickmeier; Esteban Prieto (Deutsche Bundesbank, 2016)
We assess the effects of financial shocks on inflation, and to what extent financial shocks can account for the "missing disinflation" during the Great Recession. We apply a vector autoregressive model to US data and identify financial shocks through sign restrictions. Our main finding is that expansionary financial shocks temporarily lower inflation. This result withstands a large battery of robustness checks. Moreover, negative financial shocks helped preventing a deflation during the latest financial crisis. We then explore the transmission channels of financial shocks relevant for inflation, and find that the cost channel can explain the inflation response. A policy implication is that financial shocks that move output and inflation in opposite directions may worsen the trade-off for a central bank with a dual mandate.
Keywords: E31; E44; E58; 330; financial shocks; inflation dynamics; monetary policy; financial frictions; cost channel; sign restrictions